2015
DOI: 10.1155/2015/983479
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Nonlinear Parameters of Heart Rhythm Using Short Time ECG Segments

Abstract: We propose the method to compute the nonlinear parameters of heart rhythm (correlation dimension D 2 and correlation entropy K 2) using 5-minute ECG recordings preferred for screening of population. Conversion of RR intervals' time series into continuous function x(t) allows getting the new time series with different sampling rate dt. It has been shown that for all dt (250, 200, 125, and 100 ms) the cross-plots of D 2 and K 2 against embedding dimension m for phase-space reconstruction start to level off at m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Entropy is the measure of the degree to which the occurrence of a value depends on its predecessors in the input. 11 High values of the entropy indicate high irregularity and complexity in time series data. 9 In our study, we found an increment in approximate entropy values of the experimental groups when compared with pre-drink values for 30 and 60 minutes of caffeinated beverage consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entropy is the measure of the degree to which the occurrence of a value depends on its predecessors in the input. 11 High values of the entropy indicate high irregularity and complexity in time series data. 9 In our study, we found an increment in approximate entropy values of the experimental groups when compared with pre-drink values for 30 and 60 minutes of caffeinated beverage consumption.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this adequacy, non-linear methods are being used extensively. For instance, Koichubekov et al, 11 Pivatelli et al, 12 and Neves et al 13 analysed heart rate variability by evaluating the non-linear indices, such as largest Lyapunov exponent, approximate entropy and correlation dimension in patients with hypertension, stable angina, and coronary disease, respectively. Also, Tsai et al reported that detrended fluctuation analysis shown better predictive ability for clinical outcomes when compared to traditional heart rate variability analysis methods.…”
Section: Introductionmentioning
confidence: 99%
“…There is also an inverse relationship with age with higher values in adolescent group (8 to 17 years) and lesser values starting with age group of 22 to 35 years due to increased sympathetic activity [29] . …”
Section: E Correlation Dimension (Cd)mentioning
confidence: 96%
“…Вопросы использования математико-статистических методов экстраполяции финансового положения финансовой устойчивости/нестабильности здравоохранения остаются открыты. Если в клинических исследованиях данные методы прогноза находят свое применение [6,7], и здесь можно встретить такие выражения как «неясность условий экстраполяции» (URL: http://medicalplanet.su/Patfiz/913.html), то в вопросах финансирования здравоохранения -нет.…”
Section: Evaluation Of Extrapolation Methods For Actual State Expendiunclassified